The Influence Of Leadership And Work Conflict On The Performance Of Employees Of State-Owned Enterprises (Soes) - Ventje Jeffry Kuhuparuw; Sherly Ferdinandus (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of leadership and work conflict on the performance of employees of State-Owned Enterprises (SOEs). Using a quantitative approach with a survey method, this study involves employees of State-Owned Enterprises as a population. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study show that leadership has a positive and significant effect on employee performance, while work conflicts also have a significant influence on performance. Simultaneously, leadership and work conflicts affect employee performance. This research provides important implications for the management of State-Owned Enterprises in developing an effective leadership style and managing work conflicts constructively to improve organizational performance.